Парламентська опозиція в процесах суверенізації Української РСР: Народна рада і Всесоюзний референдум 1991 р. - Підкова, Ігор; Pidkova, Ihor (Східноєвропейський національний університет імені Лесі Українки, 2014)
Розглянуто роль і місце опозиційного парламентського блоку в політичних процесах в Українській РСР, спричинених намаганням радянського керівництва легітимізувати збереження «оновленої федерації» через Всесоюзний референдум 1991 р. Простежено політичні заходи Народної ради, спрямовані на консолідацію опозиційних середовищ, формування суверенізаційних настроїв у суспільстві й законодавче закріплення перспективи становлення України як суверенної демократичної держави.

In December 1991, the Soviet government, anxious about disintegration processes in the soviet republics, initiated measures to maintain the Soviet Union as a federal state. All attempts of the official Kremlin to force signing of the new Union treaty and legitimize the process through the mechanism of the referendum democracy was perceived by oppositional parliamentary bloc "Narodna Rada" as a real threat to the sovereignty of Ukraine. For the disavowal of the true aims and consequences of the referendum for independence of the Republic, the coalitional association used the whole arsenal of political means. They included not only scientific substantiation of the legal insolvency of similar initiatives of the Kremlin but also organization of mass protests that contributed to the strengthening of sovereignty mood in the public opinion. Narodna Rada was able to consolidate most of oppositional parties and a part of sovereign-communist wing of the parliamentary majority around the idea of alternative republican plebiscite, the result of which showed the absolute public support of the sovereignty of Ukraine.
The Parliamentary Opposition on the Way to Ukrainian SSR Sovereignty: Narodna Rada and Sovie Union Referendum in 1991
Keywords: Українська РСР; Всесоюзний референдум 1991 р.; Союзний договір; Верховна Рада України; Народна рада; парламентська більшість; республіканський суверенітет; Ukrainian SSR; Union treaty; federal state; Narodna Rada; sovereign republic